(untitled) (The Journal of Modern Project Management, 2022)
The precast concrete system has grown more and more in recent years. This growth is due to benefits such as agility in the construction process, cost reduction, and better quality. However, uncertainties interdependencies during management processes are problems present in this constructive system. Given these challenges, this article proposes using technologies such as IoT, cloud computing, and RFID applied together with BIM to improve this situation. For the construction of this proposed system, it was necessary to identify user requirements, the development of a prototyping RFID reader, an application, a web platform, in addition to laboratory and field tests. Finally, the system contributed to the monitoring of quality inspection during the production, transport, and assembly stages, communication between sectors, and support in the assembly stage through the Digital twin.